Comparison Between "Theoritical" and "Measured" Values of True Digestibility of Protein and Amino Acids of Diets in Cockerels - Zuprizal (Zuprizal); M. Larbier; A. M. Chagneau (Buletin Peternakan, 1996)
Artikel dalam bentuk PDF